The mineralogical and morphological studies on archeaological pottery shreds - U. Rajesh Kumar, R. Palanivel (Recent Research in Science and Technology, 2009)
The authors are intended to focus the study on archaeological pottery artifacts to characterize the composition in terms of minerals and thereby to estimate the firing atmosphere maintained and firing temperature achieved by the artisans at the time of manufacture for the pottery shreds excavated recently from Sembiankandiyur in India. The scientific techniques FTIR, TG-DTA and SEM-EDS have been employed for the estimation of the firing temperature and conditions by studying the difference in mineral composition in the samples using spectroscopic techniques FTIR analysis. TG-DTA is considered the complementary technique to FTIR analysis in estimating firing temperature by studying the thermal characteristic reactions such as dehydration, decomposition and transformations of minerals in the course of controlled firing of the samples. SEM-EDS studies are concentrated on the morphology and elemental composition of the samples.